Loop electrosurgical excision procedure (LEEP) plus top hat for HIV‐infected women with endocervical intraepithelial neoplasia in Kenya. Issue 1 (11th December 2020) - Chung, Michael H.; De Vuyst, Hugo; Greene, Sharon A.; Topazian, Hillary M.; Sayed, Shahin; Moloo, Zahir; Cagle, Anthony; Nyongesa‐Malava, Evans; Luchters, Stanley; Temmerman, Marleen; Sakr, Samah R.; Mugo, Nelly R.; et al.
Abstract: Objective: To determine the utility of detecting endocervical cervical intraepithelial neoplasia (CIN) 2+ with endocervical curettage (ECC) and treating with loop electrosurgical excision procedure (LEEP) plus top hat (+TH) among women with HIV. Methods: Cytology was followed by coloscopy‐directed biopsy if participants had HSIL or ASC‐H and biopsy plus ECC if there were glandular cells present. CIN2/3 on ECC and/or inadequate colposcopy (ENL) was treated with LEEP+TH, while CIN2/3 on ectocervix (ECL) received LEEP alone. Recurrent CIN2+ were compared over a 2‐year follow‐up. Results: Of 5330 participants, 160 underwent ECC, 98 were CIN2/3 on ECC, and 77 received LEEP+TH. ECC detected 15 (9%) more women with CIN2/3 than biopsy alone. Women were more likely to have ENL if they were older (≥45 vs <35 years) (adjusted relative risk [aRR] 2.14; P  = 0.009) and on antiretroviral treatment longer (≥2 vs <2 years) (aRR 3.97; P  < 0.001). Over the 2‐year follow‐up, 35 (29%) ENL had recurrent CIN2+ after TH compared to 19 (24%) ECL after LEEP (hazard ratio 1.32; 95% confidence interval 0.75–2.31; P  = 0.338). Conclusion: Among HIV‐infected women, adding ECC did not increase detection of pre‐cancerous disease significantly and treatment with LEEP+TH for ENL was comparable to treatment with LEEP for ECL. Abstract : Among women with HIV, adding ECC did not increase detection of CIN and LEEP plus top hat for ENL was comparable to LEEP alone for ECL.